INDIA’S POLICIES AND POLICIES REGARDING GLOBAL WARMING AND CLIMATE CHANGE - Rawat, Meenakshi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
India is very vulnerable to the consequences of global warming and climate change, including extreme temperature rises, erratic monsoons, and more frequent cases of extreme climatic events posing significant threats to the environment, the economy, and society. Based on this motivation, this research delves into the influence that climate change policies in India pose, the impacts of political ideology, and the impacts of public awareness on climate policy adoption. A mixed-methods research design involving both quantitative and qualitative data to quantify the degree of reduction of green-house gas emissions, assess whether political party ideologies are effective for climate change action, and find out the levels of public knowledge and support on climate change policy. A stratified random sampling of 100 respondents was adopted to represent as wide demography as possible across urban and rural areas.